On‐Surface Synthesis of Cumulene‐Containing Polymers via Two‐Step Dehalogenative Homocoupling of Dibromomethylene‐Functionalized Tribenzoazulene. (29th May 2020) - Urgel, José I.; Di Giovannantonio, Marco; Eimre, Kristjan; Lohr, Thorsten G.; Liu, Junzhi; Mishra, Shantanu; Sun, Qiang; Kinikar, Amogh; Widmer, Roland; Stolz, Samuel; Bommert, Max; Berger, Reinhard; et al.
Abstract: Cumulene compounds are notoriously difficult to prepare and study because their reactivity increases dramatically with the increasing number of consecutive double bonds. In this respect, the emerging field of on‐surface synthesis provides exceptional opportunities because it relies on reactions on clean metal substrates under well‐controlled ultrahigh‐vacuum conditions. Here we report the on‐surface synthesis of a polymer linked by cumulene‐like bonds on a Au(111) surface via sequential thermally activated dehalogenative C−C coupling of a tribenzoazulene precursor equipped with two dibromomethylene groups. The structure and electronic properties of the resulting polymer with cumulene‐like pentagon–pentagon and heptagon–heptagon connections have been investigated by means of scanning probe microscopy and spectroscopy methods and X‐ray photoelectron spectroscopy, complemented by density functional theory calculations. Our results provide perspectives for the on‐surface synthesis of cumulene‐containing compounds, as well as protocols relevant to the stepwise fabrication of carbon–carbon bonds on surfaces. Abstract : Superficial interactions : On‐surface investigations of tribenzoazulene molecules functionalized with two dibromomethylene groups at the pentagon and heptagon ends reveal, after sequential annealing steps, the unambiguous formation of polymers linked by cumulene‐like bonds via selective C−C coupling induced by the sequential activation of the precursor molecules on a Au(111) surface.